Jenni Ramone, ed. The Bloomsbury Introduction to Postcolonial Writing: New Contexts, New Narratives, New Debates. Bloomsbury Academic, 2018. - Jennifer Howell (Studies in 20th & 21st Century Literature, 2019)
Review of Jenni Ramone, ed. The Bloomsbury Introduction to Postcolonial Writing: New Contexts, New Narratives, New Debates. Bloomsbury Academic, 2018. xiv + 356 pp.
Keywords: postcolonial writing; new contexts; new narratives; new debates